A triad of Uppsala internationalization of emerging markets firms and challenges: A systematic review - Paul Agu Igwe; David Gamariel Rugara; Mahfuzur Rahman (Administrative Sciences, 2022)
The economic advancement of emerging markets such as China, Brazil, and India has been regarded as one of the benefits of a globalized world. This paper revisits and evaluates the Uppsala model to teases out the process, speed, determinants, and challenges of early internationalization approaches of firms in transition and emerging markets (TEMs). Applying Systematic Literature Review (SLR), this article collects, disintegrates, and categorizes previous studies, synthesizing the theoretical models to shed light on small and medium enterprises (SMEs) characteristics, behaviour, and motives to internationalise, as well as the approaches to internationalisation. This method identified 183 articles published between 2008-2018 from 84 international journals. A triad (a set of three related things) highlights the three main features of the Integrated Uppsala Model including the basic assumptions, influential factors, and competitive strategies of firms. The findings suggest that the institutional-legal environment constitutes key barriers that firms in TEMs must overcome to develop an early internationalization strategy. It appears that internationalization literature focusing on emerging markets is biased towards China. The review identifies a need for future studies to (i) focus on emerging markets firms in Africa and South America; and (ii), provide a cross-country analysis and evaluation of internationalization strategies of TEMs.
Keywords: 350; competitive strategy; international strategy; internationalization barriers; systematic literature review; transition and emerging markets; Uppsala model